PENGARUH KADAR AIR DAN NILAI MATRIC SUCTION DALAM PENENTUAN PARAMETER TEKNIS TANAH JENUH SEBAGIAN - Herlinawati Herlinawati (PILAR, 2015)
A change partially saturated soil conditions(unsaturated) becomes saturated(saturated) as a result of the changing seasons will cause problems in the geotechnical field. Changes in water contentdue to precipitation, evaporation and evapotranspiration will affect the soil shear stress. Partially saturated soil behavioris more complex than the saturated soil. The extent to which the influence of matric suction value, a measure of the soil saturated portion of the soil shear strength changes the purpose of this study.       The soil type is silt kelempungan used in Unggaran Sta18+600. Specimens made by field density(γd, field) with variations in water content. Measurement of matric suction values was conducted using filter paper which refers to the ASTM D5298-03. Direct shear testing performed by water content variation store present changes inthe value o fmatric suction.      According to the USCS , the soil including soil type MH with field water content in the soil subgrade 50.7 % did not meet highway subgrade . The relationship between water content and degree of saturation and matric suction can be described through the SWCC curve fitting and estimates contained in SoilVision 4.19. SWCC fitting is suitable for use while Brooks and Corey Fredlund and Wilson PTF suitable to represent the SWCC curve estimation . SWCC curve estimates are quite far from the experimental data to test the filter paper still needs to be done .SoilVision program is very useful for describing both the SWCC curve fitting and estimation methods . From the research , it was found that the water content contained in the soil will affect value of matric suction , shear strength parameters of the soil and its CBR value.The higher water content or degree saturation of the soil , the more  value of matric suction , the soil shear strength parameters ( cohesion and angle of friction in )as well as its CBR value will fall.